MATHEMATICAL EDUCATION AND RURAL SCHOOL Scenarios for promoting the United Nations Agenda 2030 - Hartmann, Andrei [UNESP]; Maltempi, Marcus [UNESP]; Domingos, António (Universidade Federal de Sao Paulo, 2024)
What relationships can be established between Mathematics Education and the Sustainable Development Goals based on the study of a Rural School? This is the guiding question of a doctoral research in which we aim to develop understanding of aspects of Mathematics Education in the 17 Sustainable Development Goals of the United Nations 2030 Agenda, based on a study in a Country School located in the northwest of the state from Rio Grande do Sul/Brazil. To this end, in this article we present ideas related to research in development. To this end, we discuss theoretical ideas from Ethnomathematics in dialogue with the Sustainable Development Goals, in addition to presenting the school where the data were produced. We also discuss the results of a bibliographic survey of dissertations and theses in the area of Mathematics Education. When carrying out a search in the Brazilian Digital Library of Theses and Dissertations, we located five studies that provide initial elements for the discussion of some of the Sustainable Development Goals. These productions presented relationships with SDG 2 – Zero hunger and sustainable agriculture; SDG 3 – Health and well-being; SDG 4 – Quality education; and, SDG 12 – Responsible consumption and production. We hope to expand these relationships through the development of the thesis, contributing with reflections that concern social, economic and environmental aspects.
EDUCACIÓN MATEMÁTICA Y ESCUELA DE CAMPO Escenarios para impulsar la Agenda 2030 de Naciones Unidas
EDUCAÇÃO MATEMÁTICA E ESCOLA DO CAMPO CENÁRIOS PARA A PROMOÇÃO DA AGENDA 2030 DA ONU
Keywords: bibliographic survey; doctoral thesis; ethnomathematics; sustainable development goals